Advances in aeronautical sciences. proceedings of the First International Congress in the Aeronautical Sciences Madrid, 8-13, September 1958 - Von Karman, Theodore, 1881-1963 (International series on aeronautical sciences and space flight. Symposia., 1959)
Advances in Aeronautical Sciences.